Framing the ASEAN socio-cultural community (ASCC) post 2015: Quality and equity issues in investing in basic education in ASEAN - Tullao, Tereso S., Jr. (Animo Repository, 2015)
The paper starts with a survey on the role of basic education in society. Basic education promotes social cohesion, cultural appreciation, and civic consciousness, and bestows economic benefits to individuals and society. Although basic education does not fit into the strict conditions of public goods, governments are willing to finance and even directly operate schools because of its extensive spillover effects. Thus, it can be considered as a public good by design. The paper reviews the quality and equity considerations in the provision of basic education in the Association of Southeast Asian Nations (ASEAN) as well as the regional and national initiatives in addressing universal access and improving quality of basic education. The paper concludes with a discussion on the major issues confronting basic education and recommends the improvement of participation rates and survival rates by using developments in information and communications technology (ICT) and alternative mechanisms of financing and delivery. In addition, avenues for regional cooperation in improving quality of basic education can be done through capacity building and sharing of best practices rather than efforts towards standardisation.